Some Fixed Point Theorems for Nonlinear Set-Valued Contractive Mappings - Zeqing Liu; Zhihua Wu; Shin Min Kang; Sunhong Lee (Journal of Applied Mathematics)
Four fixed point theorems for nonlinear set-valued contractive mappings in complete metric spaces are proved. The results presented in this paper are extensions of a few well-known fixed point theorems. Two examples are also provided to illustrate our results.